2020
DOI: 10.3390/ijms21249612
|View full text |Cite
|
Sign up to set email alerts
|

Hop Bitter Acids Increase Hippocampal Dopaminergic Activity in a Mouse Model of Social Defeat Stress

Abstract: As daily lifestyle is closely associated with mental illnesses, diet-based preventive approaches are receiving attention. Supplementation with hop bitter acids such as iso-α-acids (IAA) and mature hop bitter acids (MHBA) improves mood states in healthy older adults. However, the underlying mechanism remains unknown. Since acute oral consumption with IAA increases dopamine levels in hippocampus and improves memory impairment via vagal nerve activation, here we investigated the effects of chronic administration … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 30 publications
0
11
0
Order By: Relevance
“…Significant differences were observed in CB, FI, VA, and F of the POMS2 and vitality, stability, and pleasure of the TDMS from 1 week after the intervention, suggesting that MHBAs are particularly effective for these domains of mood state. A previous preclinical study indicated that MHBAs improved mood states by activating the vagus nerve and increasing norepinephrine in the hippocampus (Fukuda, Ayabe, et al, 2019 ) and activating dopaminergic systems in the hippocampus and middle prefrontal cortex (Ano et al, 2020 ). Since decreased norepinephrine and dopamine causes fatigue, low energy, and lack of motivation (Stahl, 2002 ), MHBAs probably improve fatigue and vigor in short‐term supplementation by replenishing these neurotransmitters.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Significant differences were observed in CB, FI, VA, and F of the POMS2 and vitality, stability, and pleasure of the TDMS from 1 week after the intervention, suggesting that MHBAs are particularly effective for these domains of mood state. A previous preclinical study indicated that MHBAs improved mood states by activating the vagus nerve and increasing norepinephrine in the hippocampus (Fukuda, Ayabe, et al, 2019 ) and activating dopaminergic systems in the hippocampus and middle prefrontal cortex (Ano et al, 2020 ). Since decreased norepinephrine and dopamine causes fatigue, low energy, and lack of motivation (Stahl, 2002 ), MHBAs probably improve fatigue and vigor in short‐term supplementation by replenishing these neurotransmitters.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, dopaminergic activity in the hippocampus and middle prefrontal cortex is activated by MHBAs supplementation, which suggests that MHBAs may help alleviate the effects of social stress (Ano et al, 2020 ). Moreover, clinical studies demonstrated that supplementation with MHBAs (35 mg/day) for 12 weeks in middle‐aged and older adults improved total mood state, especially anxiety, as evaluated by the Profile of Mood States 2nd edition (POMS2); reduced feelings of fatigue, as evaluated by a visual analog scale; and reduced stress response (Fukuda, Obara, et al, 2020 ; Fukuda, Ohnuma, et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…Vulnerable mice were reported to display increased expression of DA D2 receptors in the amygdala[ 102 , 196 ] and increased levels of DA in the hippocampus and PFC[ 197 ]. However, another study found that hippocampal dopaminergic activity was inversely correlated with the level of social avoidance induced by SD and chronic treatment with hop bitter acids enhanced stress resilience[ 198 ]. Similarly, treatment with caffeine (from 14 days before until the end of SD) reverses social avoidance and anhedonia, and this pro-resilience effect of caffeine is reversed by the antagonism of DA D1 (but not D2) receptors[ 199 ].…”
Section: Advances Concerning the Neurobiological Substrates Of Resiliencementioning
confidence: 99%
“…The most important property of β‐acids that determines their behaviour in the course of the brewing process is oxidation initiated by airborne oxygen. Hop β‐acids are sensitive to oxidation reactions initialized by air (Krofta et al, 2019), and the oxidation of hop β‐acids occurs during natural ageing (Ano et al, 2020). The antidepressant activity of hops extracts can be hypothetically explained by the mechanism of lupulones (β‐acids) activating the Ca 2+ channels (Schulz et al, 2018).…”
Section: Chemical Constituentsmentioning
confidence: 99%